LAW OF TERTIUM NON DATUR - Otajonov Gаyratjon Umarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article reveals the meaning and essence of the logical law of exclusion of the third - one of the general laws of logical thinking, and also shows the significance of the law of exclusion of the third in the process of determining truth and lies.